Provision and Management of Instructional Resources in Ogun State Secondary Schools: Challenges and Solutions - Olawale Abayomi Onikoyi; Yetunde Raliat Adeola Onikoyi; Olabisi Latifat Bankole; Aminat Adejoke Nafiu (Universitas Islam Bunga Bangsa Cirebon, 2025)
Education is widely recognised as the foundation for individual empowerment and national development, yet the quality of schooling is closely tied to the adequacy and management of instructional resources. In Nigeria, and particularly in Ogun State, government secondary schools continue to grapple with persistent shortages of classrooms, laboratories, libraries, and ICT facilities. These inadequacies undermine teaching effectiveness, reduce student motivation, and deepen inequalities between urban and rural learners. Against this backdrop, this study examined the issues and possible headways for improving instructional resources in Ogun State government secondary schools. The purpose of the research was to identify recurring challenges in the provision and management of instructional resources, explain how these challenges affect the attainment of secondary education goals, and propose practical solutions that can guide policy reform. Adopting a position paper approach, the research relied on secondary data from scholarly works, government reports, and policy documents. A thematic content analysis was employed to organise insights under four categories: provision of resources, management and utilisation, emerging challenges, and reform strategies. The findings reveal that the problem of instructional resources is twofold: persistent underfunding has limited provision, while weak management practices—poor supervision, underutilization, and inadequate maintenance—further reduce the impact of what is available. In addition, inequitable distribution between urban and rural schools and the neglect of ICT resources emerged as major concerns. The study concludes that solving these issues requires not only increased funding but also reforms in accountability, equity, and teacher capacity. Its contribution lies in presenting an integrated framework that links provision with management and sustainability, offering a practical roadmap for improving public education in Ogun State and similar contexts.